An independent evaluation on the interobserver reliability and intraobserver reproducibility of Toyama classification system for cervical dumbbell tumors - Yin, Mengchen (Medicine (Baltimore), 2017)
Dumbbell tumors can not only cause the compression of cervical cord and nerve root, but also invade the important structures and the surrounding organs, causing great harm to the patient. Toyama classification that is commonly used has not been evaluated and still requires independent validation. The objectives of this study were to evaluate and analyze the interobserver reliability and intraobserver reproducibility of Toyama classification system, explore the differences, discover the shortages, and evaluate the clinical value for diagnosis. One hundred sixty-five consecutive patients of a cervical dumbbell tumor with complete clinical and radiologic data were enrolled. Six surgeons determined the classification according to Toyama system. The classification was repeated 12 weeks later. Correlation coefficient (ICC) and kappa coefficient (κ) test were used to determine interobserver reliability and intraobserver reproducibility. The interobserver reliability for Toyama classification was moderate with a value of 0.432. The interobserver reproducibility for Toyama classification was moderate with a value of 0.608. The Toyama classification has landmark value in clinical practice, but it is a relatively cumbersome system. This study shows that it has low reliability and reproducibility. Accordingly, surgical management of the resection of dumbbell cervical tumors raises several problems, including preservation of the cervical nerve root, control of the vertebral artery, and maintenance of spine. There is a need to optimize the classification in the future.